Formulating business startegic direction to enhance performance; a case of b-donat company - Reyhan Hafiz, Muhammad; Mussry, Jacky (The Indonesian Journal of Business Administration, 2019)
Abstract. B-Donat is a small company that produces cakes and donuts for middle-to-lower market segments. Founded in 2012 by Effendi Ritan with a traditional small factory. The main buyer of the product from B-Donat is reseller agents who resell the donuts to end consumers through cooperation with various stores, ranging from roadside stores to traditional food stalls. Dependence on its buyers makes the company unable to determine the price for its products and must follow the market's preference for the price of the donuts. Economic downturns and volatility such as the weakening of the Rupiah exchange rate, subsidies reduction, rapid changes in socio-economy, and also the emergence of new competitors decrease the company’s net profit margin, threaten business sustainability and reduce its performance. The company wants to jack up its revenue and get the maximum profit for all of its stakeholders through enhancing its performance. Researcher gathers key issue, and their implications for the company then give proposed solutions to achieve the desired growth of the company’s performance. The company needs a set of activities to enable it performs on the desired performance which the researcher delivers in a business strategic direction.Keywords: business strategic, donuts, developing, small and medium enterprises